IDENTIFYING STUDENTS’ READING COMPREHENSION CONSTRAINTS OF 4TH SEMESTER ENGLISH DEPARTMENT STUDENTS AT UNIVERSITY OF ISLAM MALANG - Nur Syahidah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This article aims at knowing the studentsâ€™ reading constraints from two aspects; constraints in major reading skill and difficult text type for the students. The research design in this study is descriptive quantitative reseach. The subject of this study is 4th semester students of English Department, and it consists of 30 students. The researcher used two instruments; a questionnaire and reading test. The participants took reading test after filled the questionnaire. The finding of the study is that the reading comprehension constraints faced by the students are getting the detailed information and understanding the reading text. These constraints seem inseparable since each constraint would affect the other. Then, narrative text is actually considered as the most difficult text in questionnaire result, and descriptive text is found as difficult text based on reading test result. The result is different because of the students might pay more attention on the difficult text that they have admitted in questionnaire. Therefore, the most difficult English text type is descriptive text, followed by narrative text.Keywords:Â Reading Comprehension, Reading Constraints